Principles of engineering instrumentation - Ramsay, D. ([S.l.] : Butterworth-Heinemann, 1996)
Throughout their studies, and beyond, all engineers and scientists utilise a wide range of mechanical and electronic instruments to measure, convert and monitor performance. This text aims to provide a comprehensive introduction to the necessary equipment as well as providing an insight into how they will be used in practice.